Elections 2009: what role does global development policy play in the European Parliament? - Stefan Gänzle; Sven Grimm; Christine Hackenesch; Davina Makhan (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
Among the EU institutions, the European Parliament (EP) tends to be notoriously underestimated. This is particularly true in the field of external relations, usually perceived as a prerogative of the executive. As seen from the past legislature (2004–2009) the EP showed, however, that there are several formal and informal mechanisms with which it influenced the European Union's agenda for global development, e.g. using this influence to keep Africa at the top of the list. The context for such a role was certainly more favourable when the previous legislature took office in 2004, with high growth rates worldwide and expanding emerging powers. But the ability of the EP – and Europe as a whole – to adequately respond to challenges arising from global events has since been under severe strain. Besides the need to address the climate change agenda, the Millennium Development Goals (MDG) – for which progress will be reviewed in 2010 – and humanitarian disasters as they arise, the financial and economic crisis has increased the urgency for a common European voice. If the EU aspires to be a global actor, it also needs to ensure its own internal coherence. The European Parliament has an important role to play in international development. Although it is a politically diverse actor by nature, it remains, nevertheless, a key institution for democratic scrutiny and thus legitimacy of European policies including global policy – and it should aspire to this. By seeking a more strategic engagement – as opposed to micromanagement –, the EP has the potential to further increase its impact on and contribute to a European policy for global development.
Keywords: 330